A Rare Presentation of Pancreatic Lymphoepithelial Cyst: A Case Report and Review - Grace E. Kim; Fariha Ramay; Stephanie Richards; Peter E. Darwin (Case Reports in Medicine)
Pancreatic lymphoepithelial cyst (LEC) is a rare, benign collection of keratinizing squamous epithelial cells encapsulated by lymphoid tissue. Because of its limited data and nonspecific features that can mimic malignant lesions, LECs can lead to unnecessary operations. A 62-year-old male with a known pancreatic mass presented with abdominal pain. CT scan showed an increased mass in the pancreatic head, and endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) revealed “rare fragments of benign-appearing squamous epithelium in a background of keratin debris, cyst contents, and scattered lymphocytes,” consistent with a lymphoepithelial cyst. Pancreatic LEC is an extremely rare lesion that comprises of only 0.5% of all pancreatic cysts. EUS-FNA has become the mainstay for diagnosing pancreatic LECs. Given the slow growing and benign nature, conservative management and observation is adequate for pancreatic LECs with excellent long-term outcome. With increasing number of imaging ordered by clinicians, it is anticipated that there will be a greater number of incidental pancreatic LECs detected. Thus, EUS-FNA should be utilized more frequently to help distinguish benign pancreatic LECs from premalignant or malignant lesions to avoid surgery.